(untitled) (Journal of Universal Science Research, 2024)
This article presents the principle of operation of a centrifugal pump and the classification of impellers. The geometric and kinematic parameters of the impeller were calculated, the spiral outlet was calculated, the axial force acting on the rotor and the radial force acting on the impeller were found. The impeller was designed based on the calculation results. A strength calculation of the shaft connection with the impeller was performed. The pump drive and the centrifugal pump model were selected.